Distribution and hydrolytic enzyme characteristics of Candida albicans strains isolated from diabetic patients and their non-diabetic consorts - Boriollo, M. F. G.; Bassi, R. C.; dos Santos Nascimento, C. M. G.; Feliciano, L. M.; Francisco, S. B.; Barros, L. M.; Spolidório, Luis Carlos [UNESP]; Palomari Spolidorio, D. M. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Introduction:The aim of this study was to investigate the oral colonization profile of Candida albicans strains isolated from diabetic patients and their non-diabetic consorts. In addition hydrolytic enzyme activity of these isolates was analysed.Methods:The genetic diversity of C. albicans oral isolates from 52 couples was established using isoenzyme marker and cluster analysis. Hydrolytic enzyme characteristics, namely secreted aspartyl proteinases (SAPs) and phospholipases (PLs) were also analysed.Results:Simultaneous colonization by C. albicans was observed in the consorts of 12 couples (23.1%). Patterns of monoclonal and polyclonal oral colonization by C. albicans strains were identified and the coexistence of identical or highly related strains was observed in both members of eight couples. The genetic diversity observed in the total yeast population revealed four large, genetically distinct groups (A to D) and the coexistence of strains in couples or consorts conjugally unrelated. SAP and PL activity was observed in the majority of C. albicans isolates without any association to particular strain, strain clusters (highly related isolates), or clinical characteristics of the consorts (diabetic, non-diabetic, and gender).Conclusion:Possible sources of transmission and oral propagation of groups (clusters) of strains of C. albicans can occur between diabetic and non-diabetic consorts. A conjugal genotypic identity exists in most C. albicans-positive couples, that is, both consorts share identical or highly related strains; however, this identity is not couple-specific as seen by the coexistence of clusters in couples and unrelated consorts.
Keywords: Candida albicans; diabetes mellitus; multilocus enzyme electrophoresis; oral distribution; secreted aspartyl proteinases; phospholipases